From Learner-Centered to Learner-Driven Sustainability Education - Jaana Herranen; Veli-Matti Vesterinen; Maija Aksela (MDPI, 2022)
Learner-centered sustainability education has been advocated to be used in higher education, but the pedagogy is blurry. In the discussions, also an idea of a learner-driven approach has been promoted. The aim of this study is to study how these pedagogies have been described and suggested to be used by a group of higher education students responsible for planning a teacher education course on sustainability education. This case study uses grounded theory to analyze the higher education students’ beliefs about learner-centered and learner-driven sustainability education. The data was obtained from audio-recordings of the planning process and two semi-structured interviews of five students acting as course designers. The course designers showed to have beliefs about the nature of learner-centered/learner-driven pedagogy, freedom, meaningfulness, acting and making an influence in the learning environment, the nature and ownership of sustainable development knowledge, the diversity of the learners, and pedagogical support. The results indicate that the learner-centered and learner-driven approach are fundamentally different in terms of all of the categories. In conclusion, it is suggested that the terminology concerning learner-centered and learner-driven approaches should be more precise, and sustainability education should be developed towards a more transformative, learner-driven education.